Decreased bone marrow regulatory innate lymphoid cells show a distinctive miRNA profiling in aplastic anemia. Issue 1 (1st January 2021) - Li, Yingmei; Wan, Dingming; Guo, Rong; Wang, Fang; Han, Lijie; Zhang, Danfeng; Xing, Haizhou; Cao, Weijie; Liu, Yu; Xie, Xinsheng; Yu, Jifeng; Jiang, Zhongxing
ABSTRACT: Objectives: A new regulatory subpopulation of innate lymphoid cells (ILCs), regulatory innate lymphoid cells (ILCregs), has been identified with both innate lymphoid cells and regulatory cells characteristics. The purpose of this study is to explore ILCregs and its associated miRNAs in patients with aplastic anemia (AA) by evaluating ILCregs frequency, associated miRNA quantification, and their significance. Methods: Using 4 color combinations of surface and intracellular antibody staining, the CD45+Lin−CD127+IL-10+ ILCregs from 30 healthy donors and 30 patients newly diagnosed with AA were measured by ﬂow cytometry. Bone marrow cells were studied by next-generation sequence miRNAs quantiﬁcation. Results: Our results showed that the frequency of ILCregs in bone marrow cells from healthy donors (HD) and AA patients were 0.703 ± 0.941 and 0.171 ± 0.233%, respectively. The frequencies of ILCregs in AA patients were significantly lower than that in HD ( p <0.05). miRNA detection results showed different expression patterns in the AA patient group comparing with HD. Comparing with HD, there were 52 miRNAs up-regulated and 130 miRNAs down-regulated from AA patients. Analysis of miRNAs from ILCregs associated genes demonstrated different miRNAs expression patterns between HD and AA patient. Conclusion: The present study demonstrated the deficiency of ILCregs and differential expression pattern of ILCregs gene-related miRNA in patients with AA. Further studies need to be done to explore the clinical significance of ILCregs and related miRNAs in patients with AA with large samples size and clinical follow-up.